Jejak-jejak Politik Etis Pemerintah Kolonial Belanda sebagai Alternatif Sumber Belajar IPS di Sekolah - karsiwan Pujiati (Universitas Khairun, 2018)
This research is intended to investigate the traces of the Dutch Colonial government’s legacyduring Ethical Politics era in Lampung as alternative learning materials for Social Sciencessubject. The method used in this research is a historical method with data collection techniquesthrough a literature study and documentation. Then, data was analyzed by using a qualitativeanalysis technique. Based on the results of the research, there are some points of the DutchColonial government’s legacy during Ethical Politics era in Lampung that can be used asalternative learning materials for Social Sciences subject, as follows: 1) The learning of socialsciences can be possibly integrated and correlated with the local historical themes, 2) Thepotential of the Dutch Colonial traces such as Tanjung Karang railway station, Bunker Aer,Colonization Program, Irrigation channel of Talang in Pringsewu and Metro can be used asalternative sources of learning for History subject, 3) The integration between the local historicalvalues and learning sources of History subject is expected to be not only alternative learningmaterials for Social Sciences subject, but also able to create the Social Sciences subject become afun-meaningful lesson, and it can also develop the students’ curiosity.